Review of the Oriental leafhopper genus Balala Distant, with new species and new records (Hemiptera: Cicadellidae: Hylicinae) - Tang, Jiu; Zhang, Yalin (Zootaxa, 2020)
The Oriental leafhopper genus Balala Distant is reviewed and newly recorded from Malaysia and Thailand. Four known species are redescribed and illustrated, with Balala lui newly recorded from Malaysia. And four new species are reported with descriptions and figures. A key to males of Balala species is provided. The female ovipositor of B. nigrifrons is described and photographed for the first time.